2019
DOI: 10.12688/f1000research.17447.1
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum capture of clinical pathogens using engineered Fc-mannose-binding lectin enhanced by antibiotic treatment

Abstract: Background: Fc-mannose-binding lectin (FcMBL), an engineered version of the blood opsonin MBL that contains the carbohydrate recognition domain (CRD) and flexible neck regions of MBL fused to the Fc portion of human IgG1, has been shown to bind various microbes and pathogen-associated molecular patterns (PAMPs). FcMBL has also been used to create an enzyme-linked lectin sorbent assay (ELLecSA) for use as a rapid (<1 h) diagnostic of bloodstream infections. Methods: Here we extended this work by using the EL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 44 publications
0
33
2
Order By: Relevance
“…The broad-spectrum efficacy against MRSA and multidrug-resistant bacteria suggest that this technology could represent a new alterative to antibiotics in the post-antibiotic era. Importantly, given the broad spectrum PAMPs binding capabilities of FcMBL (14), this vaccine approach should also be effective against a wide range of fungal, parasitic and viral targets. Moreover, the modular nature of the technology, and the use of lyophilized components should make this vaccination particularly useful for global and one world health applications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The broad-spectrum efficacy against MRSA and multidrug-resistant bacteria suggest that this technology could represent a new alterative to antibiotics in the post-antibiotic era. Importantly, given the broad spectrum PAMPs binding capabilities of FcMBL (14), this vaccine approach should also be effective against a wide range of fungal, parasitic and viral targets. Moreover, the modular nature of the technology, and the use of lyophilized components should make this vaccination particularly useful for global and one world health applications.…”
Section: Discussionmentioning
confidence: 99%
“…2A). To avoid this toxicity, we then captured the E. coli PAMPs from the lysate using FcMBLbeads (13,14). When FcMBL-bead-captured PAMPs containing an equivalent amount of PAMPs as the E. coli cell lysate (20.5 PAMP/mL vs 22.9 PAMPs/mL in lysate) was injected into rabbits ( Fig.…”
Section: Civax Produces Robust Humoral and Cellular Immune Responses mentioning
confidence: 99%
See 2 more Smart Citations
“…Seiler et al have further explored the use of an engineered version of MBL that demonstrated improved pathogen capture in blood and urine samples. [111] Based on these findings, there has been ongoing progress to develop extracorporeal blood filters for virus particle removal applications as well. Tullis et al demonstrated that hemodialysis treatment using a hollow-fiber cartridge that contained antibody-functionalized agarose beads could effectively remove HIV-1 virus particles and viral proteins from cell culture media and blood.…”
Section: Virus-removing Blood Filtersmentioning
confidence: 99%